THE INFLUENCE OF THE PHYSICAL ENVIRONMENT AND SERVICE QUALITY IN COFFEE SHOP ON REPURCHASE INTENTION (CASE STUDY ON JANJI JIWA COFFEE SHOP IN TOMOHON) - Saraun, Glen F.; Tumbuan, Willem J. F. A.; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2022)
The development of business in the current era occurs very quickly. The food and beverage sector are no exception. From small-scale businesses to large-scale businesses. One of the businesses that is experiencing very fast development is a Coffee Shop. According to the Coffee Association in Indonesia, the development of coffee shops in Indonesia has reached 15-20% growth. One of the coffee shop outlets in Indonesia is the Janji Jiwa Coffee Shop. Janji Jiwa must think of a strategy to be able to compete with other coffee shops plus the current situation we are facing covid-19. One of the strategies that can be used by the Janji Jiwa Coffee Shop to survive in the competition is to increase the intention to buy back from consumers so that they can get more benefits even if only from one customer. The physical environment and service quality may influence the repurchase intention of consumers. This study aims to analyze and gain a more comprehensive understanding of the effect of Physical Environment and Service Quality on Repurchase Intention in Janji Jiwa Coffee Shop. The researcher conducted this research through quantitative methods. The multiple linear regression analysis method is used to analyze the effect of the independent variable on the dependent variable. This study conducts with 100 customers from Janji Jiwa Coffee Shop in Tomohon as the respondents. The result of this study found that physical environment and service quality partially has positive effect on repurchase intention and the result also shown that physical environment and service quality simultaneously have a positive effect on repurchase intention.Â Keywords: physical environment, service quality, repurchase intention.